Mechanisms of TLR4-Mediated Autophagy and Nitroxidative Stress - Zhang, Kunli; Huang, Qiuyan; Deng, Shoulong; Yang, Yecheng; Li, Jianhao; Wang, Sutian (Frontiers in Cellular and Infection Microbiology, 2021)
Pathogenic infections have badly affected public health and development of breeding industry. Billions of dollars are spent every year to fight against these pathogens. The immune cells of the host can produce reactive oxygen species (ROS) and reactive nitrogen species (RNS) which promote the clearance of these microbes. In addition, autophagy, which is also considered as an effective way to promote the destruction of pathogens, is involved in the pathological processes. As research continues, interplay between autophagy and nitroxidative stress has become apparent. Autophagy always intertwined with nitroxidative stress. Autophagy can regulate nitroxidative stress to maintain homeostasis within in an appropriate range. Intracellular oxidation, in turn, is a strong inducer of autophagy. Toll like receptor 4 (TLR4) is one of pattern recognition receptor, which is mainly involved in regulation of inflammation during infectious diseases. A number of researches have suggested that TLR4 also is a key regulator of autophagy and nitroxidative stress. In this review, we concern the role of TLR4 in inducing autophagy and oxidation, and focus on its function in influencing autophagy-nitroxidative stress interactions.